L’enjeu paradigmatique de la relation de service au sein de la sociologie du travail - Pascal Ughetto (La Nouvelle Revue du Travail)
In addition to an approach that seeks to diversify the objects and fields of study covered in the sociology of work, in the 1990s service relationships were first and foremost considered a paradigmatic challenge where researchers were asked to conceptualise work-related problems otherwise than as typical work-related or social examples of rationalisation and resistance to rationalization. What people usually feared is that this might limit analysis to the micro-analytical level. The article argues that before returning to a relationship-oriented approach, there is a need to further explore relational approaches’ ultimately more open-ended potentialities.